Editorial. Trump’s Tariff War: Impacts and Implications for World Trade and the Global Economy - Iqbal, Badar Alam (Theoretical and Practical Research in Economic Fields, 2025)
The States President Donald Trump’s aggressive tariffs regime towards world major economies have resulted in a mixed bag of economic outcomes across the regions. Due to the Trump’s announcement, the US economy Squeezed by 0.3 per cent during quarter 1 of 2025, resulting into the first decline in last three years, Similarly, China’s factory operation goes down to a 16-month low, while Taiwan’s GDP surged 5.4 per cent on pre-tariff tech exports. Europe saw 0.4 per cent growth before tariffs hit and Canada is on track to miss GDP estimates. From the US and Europe to China and Taiwan, the repercussions of his aggressive trade policies are visible in everything from factory output to GDP forecasts. The main logic given by Trump administration for the sweeping tariff policy is to restore balance to USA’s trade relations with major trading partners and protect US industries. But the reality is somewhat different. When analysed the available economic data, trends and situation revealed a far more imbalanced scenario across regions of the world. Trade experts are of then firm opinion that sweeping rise in US tariff in 2025 are impacting in a big way the world trade. Added to this, the increase in existing tariffs may distort output patterns and also may lead to a sharp reconfiguration of world value chains, resulting in a less efficient and more opaque trade system.